A critical review of alternative measures of telecommunications service quality. Issue 3 (12th December 2019) - Abd-Elrahman, Abd-Elrahman Hassanein; Hassan, Sally Ali; El-Borsaly, Azza Abd-Elkader; Hafez, Eglal Abd-Elmoneim
Abstract : Purpose: The purpose of this paper is to review the service quality (SQ) models established in various empirical studies conducted across the world specifically applied to telecommunications services. Design/methodology/approach: This paper examines different SQ models reported in the literature applicable to the telecommunications sector. The selected 29 studies were limited to empirical English studies based on survey data and statistical methods of analysis and having the SQ construct defined from the customers' perspective. Findings: The review of various SQ models in telecommunications revealed that the meaning of SQ may have some universal aspects, as demonstrated by the similarities in the underlying dimensions as proposed in different studies. This paper lends support to the contention that the dimensions of the telecommunications SQ construct and their importance vary with the cultural and country context. A proposed model for measuring telecommunications SQ was presented as a trial to extract the best of previous models. Research limitations/implications: This paper reviews only empirical studies based on survey data and statistical methods of analysis from 2001 to 2019. Practical implications: The paper indicates that a generic instrument for measurement of SQ or even one specifically developed for telecommunications may not be applicable in its original form for all cultural contexts. The development of a customized scale, such as a modified SERVQUAL for measuring the SQ for a particular cultural or country context at that particular time, is warranted. Originality/value: The reported study describes and contrasts a large number of SQ measurement constructs and highlights the usage of dimensions.